Secrecy and Safety - Daughety, Andrew F; Reinganum, Jennifer F (American Economic Review, 2005)
We provide a model showing that the use of confidential settlement as a strategy for a firm facing tort litigation leads to lower average safety of products sold than would occur if the firm were committed to openness. A rational risk-neutral consumer's response in a market, wherein a firm engages in confidential settlements, may be to reduce demand. A firm committed to openness incurs higher liability and R&D costs, though product demand is not diminished. We identify conditions such that, if the cost of credible auditing (to verify openness) is low enough, a firm prefers to eschew confidentiality.